2004
DOI: 10.1002/asna.200410266
|View full text |Cite
|
Sign up to set email alerts
|

Stellar activity and the long‐term use of robotic telescopes

Abstract: Abstract.A number of automated and robotic telescopes are nowadays devoted to the systematic monitoring of magnetically active stars and binary systems at several astronomical institutions, all over the world, and their number is steadily increasing. Standard equipments include wide-and narrow-band photometers and, more recently, spectroscopic capabilities. The long-term time series that those telescopes are providing turn out to be of paramount importance in order to significantly progress in our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 29 publications
(25 reference statements)
7
74
0
1
Order By: Relevance
“…Such 'active longitudes' are observed in single stars such as LQ Hya, AB Dor and EK Dra (Berdyugina 2005) as well as in RS CVn binaries (e.g. Rodonò et al 2000). In shorter period systems (Prot < 1 d), active regions are preferentially located at quadrature longitudes (e.g.…”
Section: Longitude Covermentioning
confidence: 99%
See 1 more Smart Citation
“…Such 'active longitudes' are observed in single stars such as LQ Hya, AB Dor and EK Dra (Berdyugina 2005) as well as in RS CVn binaries (e.g. Rodonò et al 2000). In shorter period systems (Prot < 1 d), active regions are preferentially located at quadrature longitudes (e.g.…”
Section: Longitude Covermentioning
confidence: 99%
“…Olah et al 1994;Heckert et al 1998), whereas longer period systems show no such preference. Indeed the RS CVn binaries HD 106225 (Strassmeier et al 1994) and II Peg (Rodonò et al 2000) show a migration of active longitudes with respect to the companion star, ascribed to differential rotation. However, the lack of clearly defined active longitudes in the maps of D01, D05 and D08 suggest that such active regions are not permanent features in AE Aqr, or are at least not fixed with respect to the companion.…”
Section: Longitude Covermentioning
confidence: 99%
“…Among the most noticeable results there are the observations of high-latitude spots (see Güdel 2008, and references therein), and the high-latitude rings of toroidal field detected by Zeeman Doppler imaging (e.g., Donati et al 2003b,Catala et al 2007. Also very solar un-like behavior, such as migration of active regions toward the poles, preferred active longitudes, and "flip-flop" effect (e.g., Rodonò et al 2000, Berdyugina & Henry 2007 are typically observed. Messina (2008) has analyzed brightness and color variations in the U, B and V bands of a sample of magnetically active close binary stars on a long time scale, finding that some of them become redder when they are fainter, i.e., as is expected from the presence of active regions mainly consisting of cool spots.…”
Section: Rapidly Rotating Starsmentioning
confidence: 96%
“…Among the observing programs providing bulks of fundamental data for stellar magnetic activity studies I recall the Mount Wilson Observatory Ca ii H&K (e.g., Baliunas et al 1998), and the Lowell & Fairborn Observatories (e.g., Radick et al 1998, Messina & Guinan 2002, Lockwood et al 2007 projects, both aimed to the detection of chromospheric variability in solar-like stars, the latter dedicated also to observations of the photospheric signatures of magnetic activity. Photometric and spectroscopic monitoring have been carried out in several European observatories and institutes to get maps of spotted photospheres (e.g., Rodonò 1992, Rodonò & Cutispoto 1994, Lanza et al 1998, Rodonò et al 2000, Messina 2008, Vida et al 2007Strassmeier 2009), and of magnetic field patterns (e.g., Donati et al 2003a, Donati et al 2003b. Recently, space observations from MOST, CoRoT, and Kepler are providing very accurate optical variability data with high cadence and months duration (e.g., Walker et al 2007.…”
Section: Sources Of Long-term Data On Magnetic Activitymentioning
confidence: 99%
“…They are detached systems consisting of a G or K subgiant, and a dwarf or subgiant of spectral type F or G. Their phenomenology has been described in several reviews (e.g., Rodonò 1992;Guinan & Gimenez 1993). Long-term optical monitoring has revealed cycles of 10−20 yr in several systems (e.g., Rodonò et al 1995;Henry et al 1995;Oláh et al 1997;Lanza et al 1998;Rodonò et al 2000;Lanza et al 2001;Lanza et al 2002;Lanza et al 2006;Berdyugina & Henry 2007). Recently, Buccino & Mauas (2009) have investigated chromospheric cycles in some RS CVn systems using long-term UV data from the IUE satellite; and Messina (2008) has discussed the long-term variability of the optical colours of several systems finding in some cases evidence of a predominance of the faculae at the maximum of activity.…”
Section: Stellar Cycles From Photospheric Proxiesmentioning
confidence: 99%